The right to life – a duty to live?: a comparative analysis of the regulation of active assisted dying in England, Germany and under the ECHR - Reichstein, Angelika (2015)
This thesis addresses the question whether there is a basis for active assisted dying to fall within the protection of the European Convention on Human Rights (ECHR). With desperate individuals addressing the European Court of Human Rights (ECtHR) in order to be granted a right to die, but being denied it, the right to life is turned into a de facto duty to live. An evaluation of the concepts of dignity and autonomy will highlight the need for a right to die, to counterbalance the right to life. Seeing dignity as a subjective element means that a dignified life can only be evaluated by the person living it. If therefore a dignified death is believed to be one brought about with assistance before natural death would occur, this should not be dismissed based on a general idea of how and when people should best die. Believing in a right to a dignified life asks for a right to die in dignity. Seeing autonomy as a relational concept, meaning that for a truly autonomous life we are dependent on others and society as a whole, stresses the need for a legalisation of assisted dying. The thesis analyses the ECtHR’s approach towards assisted dying and what factors prevent it from adopting a more forthright approach towards a right to die. Based on a lack of consensus among the Member States, the Court relies on the margin of appreciation and shies away from taking a stand. While seeing that dying is a part of life and consequently falls within the ambit of Article 8, the protection of private and family life, nonetheless Article 2, the right to life, acts as a barrier to any claim for a right to die, which arguably turns the right to life in a duty to live. Looking at the legal situation in England and Germany highlights the difficulty in reaching a European consensus on assisted dying. Actively assisting someone in dying, who is unable to commit suicide unaided, is a criminal offence in both countries. However, there are significant differences between the two jurisdictions. In England, assisting someone in committing suicide is prohibited under Section 2 of the Suicide Act 1961, whereas in Germany it is in theory legally possible. Yet, in England, assistants can hope to avoid prosecution based on the Director of Public Prosecution’s guidelines of 2009, whilst in Germany assistants face prosecution based on other legal provisions like the Narcotics Act. While Germany moves towards a criminalisation of assistance in suicide offered for a fee (commercial assisted suicide), in England, debates on Bills focus on attempts to legalise some categories of assisted dying. The comparison suggests that a European consensus is not likely to be achieved in the near future. The thesis concludes that based on dignity and autonomy the national approaches towards assisted dying should be revised and legalisation should be considered. This is necessary so that the ECtHR can counterbalance the right to life with a right to die.